Stellarium Assisted Celestial Coordinate Learning to Encourage Students’ Concept Comprehension and Digital Literacy - Maulana, Muhammad Ijab; Masturi, Masturi (Universitas PGRI Semarang, 2023)
The aim of this work is to determine the understanding of concepts and digital literacy of students using the Stellarium application in learning astronomy, specifically the celestial body coordinates. The study used pre-experimental one-group pretest-posttest design. The sample consists of physics students at UNNES who were taking the Astronomy course. Data was collected through testing using a concept comprehension test and a digital literacy questionnaire. Due to the non-normal distribution of the data, hypothesis testing was conducted using the Wilcoxon test, which showed that the increase in students' concept comprehension was not significant (z-score = -1.43, p-value = 0.076). This result was confirmed by the N-gain of 8.71% (low). However, there were three indicators of the seven concept comprehension indicators tested, that showed a significant improvement, i.e. interpreting, exemplifying, and inferring. Rasch model analysis of the digital literacy questionnaire showed that students' digital literacy skills were very good and consistent with the model's prediction. Thus, the use of Stellarium in learning celestial coordinates can partially improve students' concept comprehension and digital literacy skills.Keywords: Stellarium, Celestial Body coordinates, concept comprehension, Digital Literacy.